Epidemiology of C2 fractures and determinants of surgical management: analysis of a national registry - David Acuna; Ripul Panchal; Kaysie L Banton; Carlos H Palacio; Alejandro Betancourt (Trauma Surgery & Acute Care Open, 2023)
Objective Operative management of axis fractures (C2) usually depend on the stability and location of the break and individual patient characteristics. We sought to describe the epidemiology of C2 fractures and hypothesized that determinants for surgery would differ by fracture diagnosis.Methods Patients with C2 fractures were identified from the US National Trauma Data Bank from January 1, 2017, to January 1, 2020. Patients were classified by C2 fracture diagnosis: odontoid type II, odontoid types I and III, and non-odontoid fracture (hangman’s fracture or fractures through base of the axis). The primary comparison was C2 fracture surgery versus non-operative management. Multivariate logistic regression was used to identify independent associations with surgery. Decision tree-based models were developed to identify determinants for surgery.Results There were 38 080 patients; 42.7% had an odontoid type II fracture; 16.5% had an odontoid type I/III fracture; and 40.8% had a non-odontoid fracture. All examined patient demographics, clinical characteristics, outcomes, and interventions differed by C2 fracture diagnosis. Overall, 5292 (13.9%) were surgically managed (17.5% odontoid type II, 11.0% odontoid type I/III, and 11.2% non-odontoid; p<0.001). The following covariates increased odds of surgery for all three fracture diagnoses: younger age, treatment at a level I trauma center, fracture displacement, cervical ligament sprain, and cervical subluxation. Determinants of surgery differed by fracture diagnosis: for odontoid type II, age ≤80 years, a displaced fracture, and cervical ligament sprain were determinants; for odontoid type I/III, age ≤85 years, a displaced fracture, and cervical subluxation were determinants; for non-odontoid fractures, cervical subluxation and cervical ligament sprain were the strongest determinants for surgery, by hierarchy.Conclusions This is the largest published study of C2 fractures and current surgical management in the USA. Odontoid fractures, regardless of type, had age and fracture displacement as the strongest determinants for surgical management, whereas associated injuries were determinants of surgery for non-odontoid fractures.Level of evidence III.